2021
DOI: 10.1051/0004-6361/202140443
|View full text |Cite
|
Sign up to set email alerts
|

Formation of formaldehyde through methanol-ice-mantle (CH3OH)10 bombardment by OH+ cation

Abstract: Context. Formaldehyde H2CO was the first organic polyatomic molecule discovered in the interstellar medium to have been detected in a variety of sources. However, pathways to synthesize this molecule under interstellar conditions have yet to be discussed. Aims. We carried out a systematic study to analyze the chemical processes that can explain the H2CO formation mechanism toward a decamer of methanol (CH3OH)10 as target material to mimic an ice mantle bombarded by an OH+ cation. Methods. We performed Born-Opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…In both cases, CH 2 OH was an intermediate in the formaldehyde formation pathways, among other relevant COMs. This precursor underwent secondary or tertiary processes that lead to stable COMs such as formaldehyde H 2 CO (Inostroza-Pino et al 2021). We showed that chemistry using OH + and OH • is richer than OH -, even though the H 2 CO was obtained as a stable outcome using OH -, OH • , and OH + (Inostroza et al 2019;Inostroza-Pino et al 2020.…”
Section: Hydroxymethyl Cation Ch 2 Oh +mentioning
confidence: 92%
See 3 more Smart Citations
“…In both cases, CH 2 OH was an intermediate in the formaldehyde formation pathways, among other relevant COMs. This precursor underwent secondary or tertiary processes that lead to stable COMs such as formaldehyde H 2 CO (Inostroza-Pino et al 2021). We showed that chemistry using OH + and OH • is richer than OH -, even though the H 2 CO was obtained as a stable outcome using OH -, OH • , and OH + (Inostroza et al 2019;Inostroza-Pino et al 2020.…”
Section: Hydroxymethyl Cation Ch 2 Oh +mentioning
confidence: 92%
“…We showed that chemistry using OH + and OH • is richer than OH -, even though the H 2 CO was obtained as a stable outcome using OH -, OH • , and OH + (Inostroza et al 2019;Inostroza-Pino et al 2020. Further investigations (Inostroza-Pino et al 2021) pointed toward the necessary steps to produce the CH 2 OH + intermediate from a reactive protonated methanediol. The latest intermediate underwent a dehydration reaction to yield a CH 2 OH + intermediate, which eliminated a proton to form formaldehyde:…”
Section: Hydroxymethyl Cation Ch 2 Oh +mentioning
confidence: 92%
See 2 more Smart Citations
“…The reactions of very low energy ions with an ice surface have recently been theoretically proposed as new nonenergetic reaction pathways in addition to recombination (Woon 2011(Woon , 2015(Woon , 2021a(Woon , 2021bMcBride et al 2014;Inostroza et al 2019;Singh et al 2021;Inostroza-Pino et al 2021). In most of these proposed reactions, neutral species and H 3 O + ions are spontaneously produced on the surface through reactions involving multiple water molecules.…”
Section: Introductionmentioning
confidence: 99%